Factors leading to dissemination of cutaneous anthrax: an international ID-IRI study. (July 2022) - Elbahr, U.S.; Tekin, R.; Papić, M.; Pandak, N.; Erdem, H.; Can, F.K.; Alpat, S.N.; Pekok, A.U.; Pehlivanoglu, F.; Karamese, M.; Petru, P.C.; Kulzhanova, S.; et al.
Abstract: Background: Although anthrax is a rare zoonotic infection, it still causes significant mortality and morbidity. In this multicenter study, which is the largest anthrax case series ever reported, we aimed to describe the factors leading to dissemination of cutaneous anthrax. Methods: Adult patients with cutaneous anthrax from 16 referral centers were pooled. The study had a retrospective design, and included patients treated between January 1, 1990 and December 1, 2019. Probable, and confirmed cases based upon CDC anthrax 2018 case definition were included in the study. A descriptive statistical analysis was performed for all variables. Results: A total of 141 cutaneous anthrax patients were included. Of these, 105 (74%) patients had probable and 36 (26%) had confirmed diagnosis. Anthrax meningitis and bacteremia occurred in three and six patients, respectively. Sequelae were observed in three patients: cicatricial ectropion followed by ocular anthrax (n = 2) and movement restriction on the left hand after surgical intervention (n = 1). One patient had gastrointestinal anthrax. The parameters related to poor outcome (p < 0.05) were fever, anorexia, hypoxia, malaise/fatigue, cellulitis, fasciitis, lymphadenopathy, leukocytosis, high CRP and creatinine levels, longer duration of antimicrobial therapy, and combined therapy. The last two were seemingly the consequences of dissemination rather than being the reasons. The fatality rate was 1.4%. Conclusions: Rapid identification of anthrax is crucial for prompt and effective treatment. Systemic symptoms, disseminated local infection, and high inflammatory markers should alert the treating physicians for the dissemination of the disease.